Eating in Eden : food and American utopias - Madden, Etta M., 1962-; Finch, Martha L. (At table series., 2006)
North America has provided a fertile setting for the development of distinctive foodways reflecting the diverse visions of life in the United States. This book explores the ways Americans have produced, consumed, avoided, and marketed food and food-related products and meanings to further their visionary ideals.